Human blood L lymphocytes in patients with active systemic lupus erythematosus, rheumatoid arthritis and scleroderma: a comparison with T and B cells. - Horwitz, D A (1977)
Human blood lymphocytes with high affinity Fc receptors for IgG will bind small aggregates of this immunoglobulin at 4 degrees C. These cells have been named L lymphocytes because of membrane-labile IgG determinants. L cells possess a profile of surface markers and functional characteristics which differ from T and B cells. Immunofluorescence methods have been employed to quantify L lymphocytes in subjects with connective tissue diseases and certain infections, and these values have been compared with those for T and B cells. The mean values of L lymphocytes in groups of patients with systemic lupus erythematosus, rheumatoid arthritis and scleroderma ranged between 14% and 18%; values similar to normals. Groups with acute pneumonia and tuberculosis, however, had significantly increased percentages of L lymphocytes. The absolute number of L cells was decreased in subjects with connective tissue diseases, as was the number of T and B cells. L lymphocytes in those with infections were not significantly decreased. Only L lymphocytes were depleted by immobilized antigen--antibody complexes, another characteristic which distinguishes them from T and B cells.